3D PROTOTYPING APPLIED TO DENTAL IMPLANT SURGERIES. - Machado Almada, Carlos; Mota, Sandra Regina (Brazilian Journal of Implantology and Health Sciences, 2020)
Tooth loss is one of the major problems in dentistry. With technological advances, the dental implant came to perform replacement of extracted teeth. The use of 3D impressions brought the possibility of reproducing dental arches in a reliable way, thanks to the InVesalius program that processes tomographic images, transforming them into a file capable of reproducing a dimensionally accurate prototype by printing. With regard to dentists, prototyping offered great benefits, such as clarity in surgical planning and safety in the execution of procedures, in addition to allowing the patient to elucidate the process in advance, reducing numerous dissatisfactions and doubts about the proposed treatment. Coupled with the advantages offered to the dentist and the patient, by the 3D prototype, the cost factor is of paramount importance due to its irrelevance as to the total value of a dental implant in view of the benefits offered by the use of 3D prototyping. This work presents the process of generating a three-dimensional model using the Invesalius software and its printing, with subsequent dental implant testing.